2021
DOI: 10.1007/s12672-021-00398-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological factors and survival outcomes of signet-ring cell and mucinous carcinoma versus adenocarcinoma of the colon and rectum: a systematic review and meta-analysis

Abstract: Background Histological subtypes of colorectal cancer may be associated with varied prognostic features. This systematic review and meta-analysis aimed to compare clinicopathological characteristics, recurrence and overall survival between colorectal signet-ring cell (SC) and mucinous carcinoma (MC) to conventional adenocarcinoma (AC). Methods A literature search of MEDLINE, EMBASE, Ovid and Cochrane Library was performed for studies that reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…Therefore, lymphovascular invasion is closely related to the features of aggressive tumours. While our study showed a trend towards poorer survival with all colorectal adenocarcinomas associated with lymphovascular invasion, our findings have clinical relevance in that it suggests that the presence of lymphovascular invasion is an indication for more extensive resection of the colorectal tumour [53,54,55].…”
Section: Discussionsupporting
confidence: 37%
“…Therefore, lymphovascular invasion is closely related to the features of aggressive tumours. While our study showed a trend towards poorer survival with all colorectal adenocarcinomas associated with lymphovascular invasion, our findings have clinical relevance in that it suggests that the presence of lymphovascular invasion is an indication for more extensive resection of the colorectal tumour [53,54,55].…”
Section: Discussionsupporting
confidence: 37%
“…In recent years, the survival of patients with CRC has gradually improved with the continuous update of examination and treatment methods. Colorectal signet-ring cell carcinoma (SRCC) is a rare tumor type, accounting for approximately 1% of all CRC [ 2 , 3 ]. Histologically, colorectal SRCC is characterized by the presence of nuclei that are crescent-shaped and resemble rings, hence the name, which are off-centered in over 50% of tumor cells [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Signet-ring cell carcinomas are observed in approximately 1% of colorectal carcinoma cases and are present as single cells with abundant cytoplasmic mucin. Mucinous adenocarcinomas with signet-ring cell carcinomas are distinctively different from adenocarcinoma in tumor biology, with an aggressive phenotype[ 5 ].…”
Section: Introductionmentioning
confidence: 99%